La Educación Religiosa Escolar, sentido y significado (2020)
The present article arises from the reflections about the School Religious Education (ERE) that are raised in the Group of Investigation "Religious Phenomenon" of the Catholic University of Pereira, in which the Religious Education is understood as a propitious scenario for the transformation of the human being in today's world; These reflections are presented in four moments, beginning with a look at the current state of the religious phenomenon, the crisis of meaning that is presented around it, then presents the specific of the ERE and its contribution to the meaning of life, and finally propose the ERE as a bet for building peace.